Allele Frequency of ABO Blood Group Antigen and the Risk of Esophageal Cancer. (19th June 2014) - Kumar, Narender; Kapoor, Akhil; Kalwar, Ashok; Narayan, Satya; Singhal, Mukesh Kumar; Kumar, Akhender; Mewara, Abhishek; Bardia, Megh Raj
Abstract : Background . ABO blood group and risk of squamous cell carcinoma of esophagus have been reported by many studies, but there is no discipline that had provided association with the genotype and gene frequency by population statics. Methods . We conducted a case-control study on 480 patients with squamous cell carcinoma of the esophagus and 480 noncancer patients. ABO blood group was determined by presence of antigen with the help of monoclonal antibody. Chi-square test and odds ratio (OR) with 95% confidence intervals (CIs) were calculated by statistical methods, and gene frequencies were calculated by Hardy-Weinberg model. Results . We observed significant associations between ABO genotype and squamous cell carcinoma of esophagus. OR (95% CIs) was 1.69 (1.31–2.19) for presence of B antigen allele relative to its absence (P < 0.0001 ); in female subgroup OR (95% CIs) observed at 1.84 (1.27–2.65) was statistically significant (P = 0.001 ). SCC of esophagus shows significant difference in comparison to general population; blood group B is found to be higher in incidence (P = 0.0001 ). Increased risk of cancer was observed with absence of Rh antigen (P = 0.0001 ). Relatively increased gene frequency of q [B] allele is observed more significantly in female cancer patients (P = 0.003 ). Conclusion . Statistically significant association between squamous cell carcinoma of the esophagus and ABO and Rh genotype is identified by this study. Sex and anatomical site of cancer also present with statistically significant relative association. However, larger randomised trials are required to establish the hypothesis.